The Potential of Jambu Keling (Syzigium Cumini) Leaves as A Candidate for Hypertension Herbal Therapy: A Review - Rahmaddiansyah, Refa; Kurniawan, Faishal Arif; Amriza, Muhammad Zidan; Rita, Rauza Sukma (Faculty of Medicine, Universitas Andalas, 2025)
HypertensionÂ or elevated blood pressureÂ is a serious medical condition that significantly increases the risks of heart, brain, kidney, and other diseases. The number of adults with hypertension increased day by day. Certain health conditions, such as diabetes and obesity, can also increase the risk of developing hypertension. The treatment of hypertension is lifestyle changes and medication. Patient with hypertension usually does not take their medication due to its side effects and expensive cost. Herbal therapy is very much developed lately, due to its low price, abundant availability in nature, and minimum side effects. The objective of this study is to find out the potential of Syzigium cumini leaves as a candidate for hypertension herbal therapy. This research is a literature review study using secondary data from related research. Syzigium cumini leaves contain flavonoids and/or triterpenes that exert antihypertensive effects through the combination of the vasodilatory and antioxidant activities of these classes of compounds. Syzygium cumini leaves reduce the blood pressure and heart rate of spontaneously hypertensive rats in some in vivo and in vitro studies. This antihypertensive effect is probably due to the inhibition of arterial tone by the blockade of extracellular Ca2+ influx. Keywords: Syzygium cumini, Hypertension, Herbal therapy.